The asymptotic variance of the giant component of configuration model random graphs - Ball, Frank; Neal, Peter (Institute of Mathematical Statistics, 2017)
For a supercritical configuration model random graph it is well known that, subject to mild conditions, there exists a unique giant component, whose size $R_n$ is $O (n)$, where $n$ is the total number of vertices in the random graph. Moreover, there exists $0 < ρ ≤ 1$ such that $R_n/n \convp ρ$ as $\nr$. We show that for a sequence of {\it well-behaved} configuration model random graphs with a deterministic degree sequence satisfying $0 < ρ < 1$, there exists $σ^2 > 0$, such that $var (\sqrt{n} (R_n/n -ρ)) → σ^2$ as $\nr$. Moreover, an explicit, easy to compute, formula is given for $σ^2$. This provides a key stepping stone for computing the asymptotic variance of the size of the giant component for more general random graphs.